2017
DOI: 10.5116/ijme.5918.ad11
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of residents’ and fellows’ personal finance literacy: an unmet medical education need

Abstract: ObjectivesThis study aimed to assess residents’ and fellows’ knowledge of finance principles that may affect their personal financial health. MethodsA cross-sectional, anonymous, web-based survey was administered to a convenience sample of residents and fellows at two academic medical centers.  Respondents answered 20 questions on personal finance and 28 questions about their own financial planning, attitudes, and debt. Questions regarding satisfaction with one’s financial condition and investment-risk toleran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
68
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 9 publications
5
68
1
1
Order By: Relevance
“…Our findings were similar to those of previous educational studies, where residents from various specialties were mostly described to have high educational debt and limited financial preparedness. 5,6,8,9,11 In our study, we were able to categorize residents' financial behaviors and attitudes in relation to their concern over educational debt. Our data showed that while a significant portion of residents engage in positive financial behaviors, a subset have high debt, lower levels of concern, and fewer positive financial practices compared with their peers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings were similar to those of previous educational studies, where residents from various specialties were mostly described to have high educational debt and limited financial preparedness. 5,6,8,9,11 In our study, we were able to categorize residents' financial behaviors and attitudes in relation to their concern over educational debt. Our data showed that while a significant portion of residents engage in positive financial behaviors, a subset have high debt, lower levels of concern, and fewer positive financial practices compared with their peers.…”
Section: Discussionmentioning
confidence: 99%
“…3 Surveys of residents reported low rates of financial knowledge, high levels of debt, and deficits in financial preparedness. [4][5][6] High levels of educational debt among internal medicine residents have been associated with high burnout and low quality of life. 7 Lack of financial planning during residency can have long-term effects.…”
Section: Introductionmentioning
confidence: 99%
“…The high level of resident interest in financial education found in this study is consistent with the experience of faculty who lecture on this topic . This high level of interest combined with the low levels of financial knowledge reported here and described previously suggest that this educational need is not being met by existing resources …”
Section: Discussionmentioning
confidence: 52%
“…Medical training is woefully bereft of financial education, and freshly minted pathologists-like all new physiciansare often left rudderless when it comes to navigating their personal finances. [1][2][3][4] Most trainees would rather spend time learning how to diagnose disease than translating the foreign language of finance. Meanwhile, the burden of student debt, modest resident salaries, and the societal pressures of ''physician wealth'' can lead to financial despair, depression, and burnout during training.…”
mentioning
confidence: 99%
“…Meanwhile, the burden of student debt, modest resident salaries, and the societal pressures of ''physician wealth'' can lead to financial despair, depression, and burnout during training. 2,3 The lack of fiscal knowledge can also leave pathology graduates vulnerable to monetary missteps that can impact them for the rest of their lives: allocating investments inadequately and haphazardly, sitting on debt unnecessarily, and escalating spending carelessly. Fortunately, prudent moves early in one's career can prevent these problems and set up new-in-practice pathologists for a stable financial future.…”
mentioning
confidence: 99%